Review of the genus Alysia Latreille (Hymenoptera, Braconidae, Alysiinae), with description of six new species from China - Zhu, Jia-Chen; van Achterberg, Cornelis; Chen, Xue-Xin (Zootaxa, 2018)
Six new species of Alysia Latreille are described and illustrated from China, i.e., Alysia hebeiensis sp. n., A. macularis sp. n., A. melasoma sp. n., A. polita sp. n., A. sparsa sp. n., and A. stenopos sp. n. Also, six species are reported as new to China: Alysia incongrua Nees, 1834, A. lucia Haliday, 1838, A. lucicola Haliday, 1838, A. sirin Belokobylskij, 1998, A. umbrata Stelfox, 1941 and A. vladik Belokobylskij, 1998. A key to the known species of Alysia Latreille from China is provided.